Perbedaan Indeks Kebutuhan Perawatan Periodontal (CPITN) antara Pengguna Kontrasepsi Metode Oral dan Suntik di Departemen Periodonsia RSUB Periode November-Desember 2024 - Elizabeth Chandradewi Purnamasari; Ega Lucida Chandra Kumala; Nungky Devitaningtyas; Dyah Nawang Palupi Pratamawari (Universitas Diponegoro, 2026)
Background: Hormonal contraceptives can trigger periodontal inflammation through changes in estrogen and progesterone levels, thereby increasing the risk of damage to the tooth-supporting structures and elevating periodontal treatment needs. Objective: To analyze the differences in periodontal treatment needs between users of oral and injectable hormonal contraceptives based on the Treatment Needs (TN) classification derived from Community Periodontal Index of Treatment Needs (CPITN) scores. Methods: This analytical observational study with a cross-sectional design was conducted on 18 women using hormonal contraceptives, divided into two groups: 9 oral contraceptive users and 9 injectable contraceptive users at the Department of Periodontology, RSUB, Malang. Periodontal examinations were performed using a WHO probe, and the results were categorized according to Treatment Needs. The Mann–Whitney U test was used to assess differences between groups. Results: The Mann–Whitney test showed a significant difference in periodontal treatment needs (p = 0.006) between oral and injectable hormonal contraceptive users. Conclusion: There is a difference in CPITN-based periodontal treatment needs between oral and injectable hormonal contraceptive users visiting the Periodontology Department of RSUB, Malang, during November–December 2024, with oral contraceptive users more frequently classified in TN 3 and injectable contraceptive users in TN 2.